2014
DOI: 10.1089/met.2013.0039
|View full text |Cite
|
Sign up to set email alerts
|

Increased Prevalence of Metabolic Syndrome in Patients with Psoriatic Arthritis

Abstract: This study demonstrated an increase in the frequency of metabolic syndrome, which is a major risk factor for atherosclerosis in patients with PsA. Patients with PsA should be closely followed in terms of cardiovascular events, and aggressive treatment should be performed for both cardiovascular risk factors and the disease itself.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
32
2
1

Year Published

2014
2014
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 33 publications
(36 citation statements)
references
References 22 publications
1
32
2
1
Order By: Relevance
“…A limited number of previous studies have indicated that the prevalence of MetS in patients with PsA is between 23.5% and 58.1% (21)(22)(23)(24). There is one study that investigated the prevalance of MetS in a small number of patients with PsA in Turkey (9). The authors of that study reported that the prevalance of MetS in patients with PsA using NCEP criteria was 40.6%, which was similar to our results.…”
Section: Discussionsupporting
confidence: 90%
See 1 more Smart Citation
“…A limited number of previous studies have indicated that the prevalence of MetS in patients with PsA is between 23.5% and 58.1% (21)(22)(23)(24). There is one study that investigated the prevalance of MetS in a small number of patients with PsA in Turkey (9). The authors of that study reported that the prevalance of MetS in patients with PsA using NCEP criteria was 40.6%, which was similar to our results.…”
Section: Discussionsupporting
confidence: 90%
“…Studies on the prevalence of MetS in Turkey ranges from 26.5% to 42.6% (6)(7)(8). Recent studies have shown that the prevalence of MetS and cardiovascular diseases (CVDs) increases in patients with PsA and that CVDs are the most common cause of death in patients with PsA (9)(10)(11)(12)(13)(14). The aim of this study was to identify the prevalence of MetS and the degree of CVD risk in patients with PsA compared to patients with RA in a Turkish population.…”
Section: Introductionmentioning
confidence: 99%
“…However, after restricting the analysis to those without IBD, AS or RA, the findings remained substantially unchanged. An association between obesity, including the metabolic syndrome, and PsA is well established . In our cohort, a greater proportion of pregnancies with PsA were complicated by obesity than non‐PsA pregnancies but the frequency of pre‐pregnancy hypertension was low.…”
Section: Discussionmentioning
confidence: 66%
“…This screening must be performed annually in patients receiving topical treatment for their psoriasis and every 6 months in patients on systemic treatments. psoriasis have an increased prevalence of metabolic syndrome, with a positive relationship with the severity of psoriasis(120)(121)(122). To detect the existence of this condition, clinicians must assess the presence of three or more of the following criteria defined by the National Cholesterol Education Program (ATP III) (119): abdominal obesity; tryglicerides >150 mg/dL or specific treatment; HDL-C <40 mg/dL in men or <50 mg/dL in women or specific treatment; BP >130/85 mm/Hg or treatment for hypertension; fasting glucose >100 mg/dL.…”
mentioning
confidence: 99%